Cytotoxic effect of 2,3-dihydro-6-hydroxy-2-methylenenaphtho[1,2-b] furan-4,5-dione compound from the bark of faloak (Sterculia quadrifida R.Br) in breast cancer cells T47D - Rollando Rollando; Rokiy Alfanaar (Pharmaciana, 2017)
Faloak (Sterculia quadrifida R.Br) is used empirically by residents of East Nusa Tenggara for drug plant. The information of the active compound contained in the faloak bark yet specifically published. This study aims to determine the active compound contained in the faloak bark that have cytotoxic activity to T47D breast cancer cells. Extraction process using maceration method, isolation process using gradien isolation method, elusidation using combination of information of IR spectra, 1D-NMR, 2D-NMR and LC-MS, and cytotoxic activity test on T47D breast cancer cells using MTT method. The isolation result obtained that isolate of naphthoquinone derivative compound is 2,3-dihydro-6-hydroxy-2-methylenenaphtho [1,2-b] furan-4,5-dione with IC50 value on T47D breast cancer cell was 9,88 Âµg/mL and with an index selectivity value was 30,23.Â